Being overindebted and overweight in Switzerland – A largely unexplored association in an understudied population - Oliver Hämmig (PLoS ONE, 2026)
Objectives Research on overindebtedness in general and on the relationship between overindebtedness and being overweight or obese in particular is extremely rare or practically nonexistent although both phenomena have shown an increasing trend in recent years and are expected and found to be more prevalent among lower social classes and educational levels. However, no such study for Switzerland has ever been conducted until now. Methods Survey data collected in 2019 from 219 overindebted adult clients of four official debt advisory centers in the Canton of Zurich were used and linked with a sample of 1,997 respondents of the Swiss Health Survey 2017 of the same age and canton of residence. The entire study population included a total of 2,216 adult individuals. Contingency tables with relative frequencies were calculated to study differences between the two subsamples. Furthermore, logistic and Poisson regression analyses were performed to calculate unadjusted and multiple-adjusted odds ratios and risk ratios as proxies and measures for the relative risk of being overweight or obese among overindebted people. Results The prevalence rates of being overweight and having a body mass index (BMI) of 25+ and particularly of being obese (BMI of 30+) were significantly higher among overindebted individuals (BMI ≥ 25: 46%, BMI ≥ 30: 15%) than predominantly non-overindebted people (BMI ≥ 25: 38%, BMI ≥ 30: 9%). Overindebtedness increased the odds or the relative risk for such unfavourable body weights by 20% to 36% (overweight) and by 59% to 70% (obesity) depending on the effect measure considered. This was found regardless of overindebted individuals’ sex, age and educational level and independent of the fact that they have a comparably very low sense of control, feel lonely much more often and show much more often moderate to severe depressive symptoms. Conclusions Measures of effect or association found were statistically significant at least for obesity, but smaller than expected and somewhat under- and simultaneously overestimated in view of the younger average age and the lower educational level of the overindebted individuals.